The dictatorship as reference: the discourse of rock'and roll in the Argentine and framework of democratic transition. - Secul Giusti, Cristian (Facultad de Periodismo y Comunicación Social, 2016)
This paper presents a preview of doctoral thesis research on the discursive construction of freedom which focus the lyrics of rock-pop Argentina during the period 1982-1989, since the end of the tragic Falklands War until the end of the first government of the recovered democracy.The research contributes to reflection on the speeches of the rock-pop Argentina, pretending to investigate and understand the continuities and ruptures that set the lyrical speeches. Therefore, the analysis of linguistic discourse works as a field of qualitative research, from French side, can articulate interpretative guidance language, centralized in declarative frameworks and related to exploratory studies of discourse context.In these cases, the discursive construction of the freedom working from the diversity and retakes as a framework for discussion at a stage of transformation. Thus, a body of 40 (forty) letters Argentine rock-pop with the intention to form a heterogeneous and detailed on the topics of freedom map, contiguous, democratic aims. Thus creates the lyrics recognize ways of seeing and feeling that mutate and social highlight critical arguments, linked to inequalities and complexities of a country under reconstruction.With respect to the Argentine rock culture, we understand that prospects are transcendental addressed to warn dialogic and discursive tables are turned and fed back to the social space of time «democratic transition». As a complex cultural phenomenon, the Argentine rock represents a compendium of experiences that go beyond the purely musical and lyrical.Fundamentally, the rock produced domestically produced and causes linked from the field of culture, identities and worldviews turning to deal with the conventions. In light of this, it is noted that since its inception has worked as a youth counterculture vehicle identification shown rebel, rebellious means, and that from its link with the pop aesthetic of the eighties, are built upon the provocation and transgression.